DERADIKALISASI ATAS PEMAHAMAN AL-QUR’AN (ANALISIS SEMANTIK DAN KONTEKS HISTORIS TERHADAP AYAT-AYAT TENTANG JIHĀD DAN QITĀL) - Tahir, Muhammad Suaib (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
A mistake in understanding these verses about jihād and qitāl can trigger the emergence of various radical ideas. Someone with radical views only understands these verses textually, so he will assume that all non-Muslims must be fought. One of the efforts to deradicalize such an understanding is to study and analyze the verses of jihad and qital with semantic analysis and historical context. Semantic analysis is used to analyze variations and contexts of word meanings from key words in the Qur'an. The keywords analyzed in this study are the terms "al-qitāl and al-jihād". Based on this analysis, in the Mecca period, neither of these two terms were synonymous with war or violence. In addition, these two terms experienced several shifts in meaning when entering the Medina period. Meanwhile, the historical context is used to trace various events that accompanied the revelation of the Qur'an. The decline of these verses was motivated by the negative behavior of polytheists towards Muslims which was carried out continuously. The revelation of these verses is the last alternative to defend against the attacks of the polytheists. This type of research is library research, while the main reference sources are verses about jihād and qitāl. It is hoped that this research can straighten out various radical ideas about the verses of jihad and qitāl and can become part of the treasures of religious moderation for Indonesian citizens